2019
DOI: 10.3390/rel10050316
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health among Italian Nichiren Buddhists: Insights from a Cross-Sectional Exploratory Study

Abstract: Religiosity/spirituality is generally considered as a powerful tool for adjusting and coping with stressors, attributing purposes and meanings (either existential/philosophical, cognitive, or behavioral ones) to daily situations and contexts. While studies generally investigate these effects in Judaism and Christianity believers, there is a dearth of data concerning oriental religions. We sampled from Italian Nichiren Buddhists, the most widespread branch of Buddhism in Italy (n = 391). Participants were Buddh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Having observed no differences between Catholics and Atheists, the Authors concluded that what is determinant for the greater psychological resources of Buddhists, is the religious practice, that is the assiduous chanting of Nam-Myoho-Renge-Kyo and practice within a community of believers. Another study published in 2019 (Bragazzi et al 2019), was conducted on 391 practitioners of Nichiren Daishonin's Buddhism in Italy; the results were consistent with those of the previous study. Buddhist subjects made use of adaptive coping strategies, had a predominant internal locus of control, and showed a low psychopathological profile when compared with the normative standard scores.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Having observed no differences between Catholics and Atheists, the Authors concluded that what is determinant for the greater psychological resources of Buddhists, is the religious practice, that is the assiduous chanting of Nam-Myoho-Renge-Kyo and practice within a community of believers. Another study published in 2019 (Bragazzi et al 2019), was conducted on 391 practitioners of Nichiren Daishonin's Buddhism in Italy; the results were consistent with those of the previous study. Buddhist subjects made use of adaptive coping strategies, had a predominant internal locus of control, and showed a low psychopathological profile when compared with the normative standard scores.…”
Section: Discussionsupporting
confidence: 87%
“…The word Nam derives from the Sanskrit word namas and means "devotion". Myoho-Renge-Kyo is the title of the Lotus Sutra in Japanese (The Major Writings 1979a;Watson, 1993;Giannini et al 2018;Bragazzi et al 2019). A simplified translation in English could be "Devotion to the Mystic Law of the Lotus Sutra".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Buddhism in Italy is the third most widespread and practiced religion, after Christianity and Islam. Among the different denominations, followers of Nichiren Daishonin Buddhism constitute the largest group with 75,000 members which is about half of the whole Italian community of Buddhist believers (Bragazzi et al, 2019). It is worth noting that Nichiren Daishonin Buddhism is a religion officially recognized by the Republic of Italy.…”
Section: Religious Chanting a Practice Different From All Othersmentioning
confidence: 99%